Theory and Applications of Ontology: Philosophical Perspectives
XV, 415 p.
Keywords: Ontology was once understood to be the philosophical inquiry into the structure of reality: the analysis and categorization of ‘what there is’. Recently, however, a field called ‘ontology’ has become part of the rapidly growing research industry in information technology. The two fields have more in common than just their name. Theory and Applications of Ontology is a two-volume anthology that aims to further an informed discussion about the relationship between ontology in philosophy and ontology in information technology. It fills an important lacuna in cutting-edge research on ontology in both fields, supplying stage-setting overview articles on history and method, presenting directions of current research in either field, and highlighting areas of productive interdisciplinary contact. Theory and Applications of Ontology: Philosophical Perspectives presents ontology in philosophy in ways that computer scientists are not likely to find elsewhere. The volume offers an overview of current research traditions in ontology, contrasting analytical, phenomenological, and hermeneutic approaches. It introduces the reader to current philosophical research on those categories of everyday and scientific reasoning that are most relevant to present and future research in information technology.